2012
DOI: 10.1021/cm302642g
|View full text |Cite
|
Sign up to set email alerts
|

Europium-Doped TiO2 Hollow Nanoshells: Two-Photon Imaging of Cell Binding

Abstract: A simple scalable method to fabricate luminescent monodisperse 200 nm europium doped hollow TiO2 nanoshell particles is reported. Fluorophore reporter, Eu3+ ions, are incorporated directly in the NS matrix, leaving the surface free for functionalization and the core free for payload encapsulation. Amine functionalized polystyrene beads were used as templates, and the porous walls of europium doped titania nanoshells were synthesized using titanium(IV) t-butoxide and europium(III) nitrate as reactants. X-ray di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(27 citation statements)
references
References 101 publications
0
27
0
Order By: Relevance
“…The confinement of the molecular material under the template mesh may also result from a combination of Brownian motion and Van der Waals interactions in the solvent [41]. Also changes in the surface tension and polarity of the solvent are due to the interaction between the specific parameters of the solution and the two solid interfaces (glass and the Cu grid) inducing Bénard-Marangoni instabilities in the liquid films [9][10][11][12]. Obviously, this indicates that the radius R of the formed nanoparticles depends on the starting film thickness h. Specifically, larger h will imply a larger R (as the law R / p h) [42].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The confinement of the molecular material under the template mesh may also result from a combination of Brownian motion and Van der Waals interactions in the solvent [41]. Also changes in the surface tension and polarity of the solvent are due to the interaction between the specific parameters of the solution and the two solid interfaces (glass and the Cu grid) inducing Bénard-Marangoni instabilities in the liquid films [9][10][11][12]. Obviously, this indicates that the radius R of the formed nanoparticles depends on the starting film thickness h. Specifically, larger h will imply a larger R (as the law R / p h) [42].…”
Section: Resultsmentioning
confidence: 99%
“…Besides, embedding a lanthanide complex in a hybrid matrix is also favorable for its unique optical properties such as long fluorescence lifetime and good luminescence efficiency combined with high photochemical stability of the hosts. Furthermore, titania is an excellent material for Eu 3+ being highly transparent to visible light and due to its thermal, chemical, and mechanical properties and several synthetic approaches of Eu 3+ doped TiO 2 films, nanoparticles, and particles have been reported [9][10][11][12]. The ability to pattern functional materials at different length scales is therefore essential for many research fields including electronic and optoelectronic devices [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…180,181 However, Wataha et al reported the successful delivery of MST metal ions to monocytes and fibroblast cells, and affected the cellular functionality. 184 This system could provide scaffolds for cancer theranostics if the anticancer agent is coupled with the TiO 2 nanoshells. However, later on it was found that it can be efficiently bound to biologically active metals.…”
Section: Nano-tio 2 For Theranosticsmentioning
confidence: 99%
“…Last step is calcination process, which has a dual function: the removal of carbon spheres cores and formation of hollow crystalline structures from Ln(OH)CO 3 precursor layer. Besides carbon spheres, other hard templates (polystyrene, silica spheres, and melamine formaldehyde) are also applied for the fabrication of hollow spheres ,, , …”
Section: Fabrication Strategies For Single‐phase Lanthanide‐doped Holmentioning
confidence: 99%